PENGARUH PENGEMBANGAN ORGANISASI DAN PEMBINAAN PEGAWAI TERHADAP PRESTASI KERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN TULANG BAWANG BARAT - . Supriyanto; Ade Aldiansyah Zaedar (Universitas Bandar Lampung (UBL), 2019)
Factors that can improve employee work performance is organizational development and employee coaching. The purpose of this research is to analyze the influence of organizational development and employee guidance on employee performance at the Regional Secretariat of Tulang Bawang Barat Regency both partially and simultaneously. The data collection techniques in this study are observations, questionnaires and documentation. The samples in this study amounted to 50 employees. In this research use qualitative and quantify data analysis.In general, the results of this study are as follows: 1) The development of the organization has positive influence on the work achievement of employees at the Regional Secretariat of Tulang Bawang Barat Regency, based on hypotheses test obtained t count of 3.621 with a significant rate of 0.001 because the probability or significant level is much smaller than 0.05. 2) Employee coaching has a positive effect on employee work performance in the Regional Secretariat of Tulang Bawang Barat Regency. Based on the hypothesis test, the employee coaching variable can be calculated to be 3,665 with a significant level of 0,000, because the probability or significant level is far less than 0.05. 3) The development of organization and coaching of employees jointly positively influence the performance of employees at the Regional Secretariat of Tulang Bawang Barat Regency, based on test Anova or F test at can F count of 17.850 with the level Significant of the 0.000, because the probability or the significant level is much less than 0.05.